2017
DOI: 10.1055/s-0037-1608822
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a New Web-Based System for Point-of-Care Implant Documentation in Total Knee Arthroplasty

Abstract: Implant documentation in total knee arthroplasty (TKA) must be both accurate and comprehensive. A new system enables surgeons to complete a secure, web-based operative report for each surgery. This study evaluated implant documentation using this system and hypothesized that it would be as reliable as the current standard. This was a retrospective study of all primary and revision TKA performed at a single academic institution from January 1, 2015 to March 31, 2015, by eight adult reconstruction surgeons who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 7 publications
1
21
0
Order By: Relevance
“…2;4;21 As of February, 2018, OME is used by 57 surgeons at 10 sites within the Cleveland Clinic Health System to document surgical details and PROMs on 97% of 21,500 elective knee, shoulder, and hip surgeries. Validation studies for OME in total knee arthroplasty, 21 total hip arthroplasty, 4 ACL and meniscus repair have demonstrated excellent performance of this new system in point-of-care implant documentation. Having developed and now validated the OME system for data collection, one of our future objectives is to use the OME system to create a standardized operative report and integrate with EMR systems to replace the existing methods of creating operative reports.…”
Section: Discussionmentioning
confidence: 99%
“…2;4;21 As of February, 2018, OME is used by 57 surgeons at 10 sites within the Cleveland Clinic Health System to document surgical details and PROMs on 97% of 21,500 elective knee, shoulder, and hip surgeries. Validation studies for OME in total knee arthroplasty, 21 total hip arthroplasty, 4 ACL and meniscus repair have demonstrated excellent performance of this new system in point-of-care implant documentation. Having developed and now validated the OME system for data collection, one of our future objectives is to use the OME system to create a standardized operative report and integrate with EMR systems to replace the existing methods of creating operative reports.…”
Section: Discussionmentioning
confidence: 99%
“…However, the OME data collection tool and resultant datasets have been previously validated for multiple surgical interventions and used in a growing number of contemporary studies. 7-12,15-17 Curtis et al 8 investigated the completion rates and agreement measures between OME- and EMR-based control datasets capturing peri/intraoperative details of primary total hip arthroplasty. The authors reported that the OME dataset demonstrated significantly higher completion rates in 41% of the evaluated variables.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established its effectiveness in hip, knee, and shoulder surgeries, but it has yet to be proven in hand surgery. 7-12…”
Section: Introductionmentioning
confidence: 99%
“…10 The OME system is a prospectively collected patient-reported outcomes database that leverages the Research Electronic Data Capture software (REDCap, Nashville, Tennessee) 11 and has been previously established as a reliable tool for capturing patient-reported data, including assessments of joint-specific pain function, and knee-related and general health-related QOL; general demographic characteristics; and surgeon-collected data, including patient demographic characteristics, surgical history, and surgical procedure details. [12][13][14] The STROBE (Strengthening the Reporting of Observational Studies in Epidemiology) statement recommendations were followed. 13,15…”
Section: Study Design and Data Sourcementioning
confidence: 99%
“…[12][13][14] The STROBE (Strengthening the Reporting of Observational Studies in Epidemiology) statement recommendations were followed. 13,15…”
Section: Study Design and Data Sourcementioning
confidence: 99%